Safety Climate Associated with Adverse Events in Nursing Homes: A National VA Study. (20th August 2020) - Quach, E.; Kazis, L.; Zhao, S.; Ni, P.; Clark, V.; McDannold, S.; Hartmann, C.
Abstract : Adverse events in health care are leading causes of morbidity and mortality, prompting health care organizations to investigate their antecedents. In nursing homes, safety climate—how staff typically think about safety and act on safety issues—is a potential contributor to adverse events, particularly pressure ulcers, falls, and falls‐related injuries. Yet, research to date is equivocal as to whether a more positive safety climate improves safety for residents living in nursing homes. We conducted a cross‐sectional analysis of the association between safety climate and adverse events, measured in 2017 and 2018 in 56 VA Community Living Centers (CLCs, or nursing homes) nationwide. Safety climate was measured by the previously validated Community Living Center Employee Survey on Resident Safety (CESARS), completed by nurses, nursing assistants, and clinicians. The CESARS has seven domains: safety priorities, supervisor commitment to safety, senior management commitment to safety, personal attitudes about safety, environmental safety, co‐worker interactions around safety, and global rating of CLC; higher CLC‐level domain scores indicate better ratings. 2017‐18 Minimum Data Set (MDS) measured four CLC‐level adverse events: percent of residents who had any falls, major injuries from falls, catheter use, and new/worsened pressure ulcers. Beta‐logistic regression models with random effects were used to examine the impact of staff‐specific safety climate domain scores on each adverse event, adjusted by year (2017/2018) and CLC‐level characteristics (CLC's operating beds, nursing staffing level, and employee satisfaction/engagement). 1397 and 1645 VA CLC staff responded to the CESARS in 2017 and 2018, respectively. There were significant associations between all four adverse events and three of the safety climate domains: expected, inverse associations with two domains and unexpected associations with one domain ( P  < .05). Better ratings of supervisor commitment to safety and environmental safety were each associated with lower rates of three out of the four adverse events, as expected. That is, better ratings of supervisor commitment to safety were significantly associated with lower rates of (1) falls (OR 0.33, 95% CI 0.11‐0.97, clinicians), (2) major injuries from falls (OR 0.33, 95% CI 0.11‐0.97, clinicians), and (3) catheter use (OR 0.42, 95% CI 0.21‐0.85, nurses). Better ratings of environmental safety were significantly associated with lower rates of (1) major injuries from falls (OR = 0.48, 95% CI 0.24‐0.93, nurses), (2) catheter use (OR 0.55, 95% CI 0.32‐0.93, nursing assistants), and (3) pressure ulcers (OR 0.23, 95% CI 0.09‐0.61, clinicians). Better global CLC ratings were unexpectedly associated with higher rates of only catheter use. No other safety climate domains had significant associations. In summary, supervisor commitment to safety (eg, supervisor responsiveness to safety concerns) and environmental safety (eg, presence of grab bars in bathrooms) emerged as elements of safety climate central to lower rates of adverse events in nursing homes. The role of safety climate in lower rates of adverse events was observed across all three groups of frontline staff. Our study thus suggests the potential of safety climate to impact resident safety outcomes. Improving environmental design and supervisory practices with frontline staff could reduce adverse events in nursing homes. Department of Veterans Affairs.